Cover Image, Volume 30, Issue 2. (16th January 2017) - Yin, Ting; Peeters, Ronald; Feng, Yuanbo; Liu, Yewei; Yu, Jie; Dymarkowski, Steven; Himmelreich, Uwe; Oyen, Raymond; Ni, Yicheng
Abstract : The cover image, by Ting Yin et al., is based on the RESEARCH ARTICLE Characterization of a rat orthotopic pancreatic head tumor model using three-dimensional and quantitative multi‐parametric MRI, DOI:10.1002/nbm.3676 .